2016
DOI: 10.1038/onc.2015.491
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 is elevated in medulloblastoma and drives proliferation in Sonic hedgehog-dependent cerebellar granule neuron progenitor cells and medulloblastoma cells

Abstract: Post-natal proliferation of cerebellar granule neuron precursors (CGNPs), proposed cells-of-origin for the SHH-associated subgroup of medulloblastoma (MB), is driven by Sonic Hedgehog (Shh) and Insulin-like Growth Factor (IGF) in the developing cerebellum. Shh induces the oncogene Yes-associated protein (YAP), which drives IGF2 expression in CGNPs and mouse Shh-associated medulloblastomas. To determine how IGF2 expression is regulated downstream of YAP, we carried out an unbiased screen for transcriptional reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 74 publications
2
26
0
Order By: Relevance
“…Cell growth is strictly regulated and controlled by a careful balance of regulatory systems. Abnormal cell growth is the critical feature of malignant tumors . In this study, we observed a significant suppression of cell proliferation of chordoma cell lines after YBX1 knockdown, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Cell growth is strictly regulated and controlled by a careful balance of regulatory systems. Abnormal cell growth is the critical feature of malignant tumors . In this study, we observed a significant suppression of cell proliferation of chordoma cell lines after YBX1 knockdown, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…For example, human helicase RECQL4 drives cisplatin resistance in gastric cancer by activating an AKT-YB1-MDR1 signaling pathway 23 and the SHH:YAP:YB1:IGF2 axis as a powerful target for therapeutic intervention in medulloblastomas. 24 Also,YB-1 associates with thousands of nonpolyadenylated short RNAs (shyRNAs) that are further processed into small RNAs (smyRNAs). 25 Moreover, ENZ-induced HER2 overexpression was dependent on AKT-YB1 activation and modulated AR activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the Hippo/YAP pathway can crosstalk with other signalling pathways to regulate a series of biological functions in cancer, which is greatly depends on the important role of YAP that is not only mediated by the upstream signal molecule, but can also regulate a series of targets via interacting with transcription factors. By analysing studies published in recent years, we can summarize a complex regulatory network in which YAP is involved in a series of signalling pathways (Figure 1 ), such as those involving TGF-β/SMAD [ 67 , 68 ], Wnt/β-catenin [ 69 , 70 ], epidermal growth factor receptor (EGFR) [ 39 , 71 ], PI3K-AKT [ 72 , 73 ], NF-κB [ 69 , 74 ], Sonic Hedgehog (Shh) [ 75 , 76 ], mTOR [ 77 , 78 ], IL6 receptor (IL-6R) [ 79 , 80 ], GPCR [ 81 , 82 ], and Notch [ 83 , 84 ].…”
Section: Introductionmentioning
confidence: 99%